PENGARUH PEMBERIAN EKSTRAK KULIT BUAH RAMBUTAN (Nephelium lappaceum) TERHADAP GAMBARAN MORFOLOGI SPERMATOZOA TIKUS JANTAN GALUR WISTAR (Rattus norvegicus) DENGAN INDUKSI PAKAN TINGGI LEMAK - Iqlima Luthfiya (2020)
Excess amounts of high fat foods and lack of physical activities can be a cause of an obesity. Obesity can increased Reactive Oxygen Species (ROS), so it could affect the process of spermatogenesis. Rambutan peel is known to have antioxidant and anti-obesity effects. The study was aimed to determine of the effectiveness of rambutan peel extract on the percentage of abnormal sperm morphology of male wistar rats induce with high fat diet. The research method uses a true experimental post control group design on 30 male Wistar rats aged 9-12 weeks and weighing ± 200-400 grams. Samples were divided into 5 groups, with total limit of the research is 82 days. Group 1 : induced with high fat diet only, Group 2 : only given rambutan peel extract at a dose 30mg/kgBW, Group 3, 4 and 5 : induced with high-fat diet and rambutan peel extract at dose 15 mg/kgBW, 30 mg/kgBW, 60 mg/kgBW. The results were assessed after the research done. The statistic analysis using Anova One Way. The outcome result shows p-value 0,001. The result showed that rambutan peel extract has antioxidant compounds, so it can prevent abnormal sperm morphology of male wistar rats with the greatest efficacy at dose of 15mg/kgBW.